Revisión de los principales modelos de diseño instruccional (Review of main instruccional design models) - Jardines Garza, Francisco Javier (Facultad de Contaduría Pública y Administración U.A.N.L., 2011)
Abstract. The intention of this document is to describe and to analyze the taxonomy of Instructional Development models (ID) elaborated by Kent L. Gustafson and Robert Maribe Branch (2002). A taxonomy of ID models is useful because it allows to identify and to analyze in a more expeditious way each model and help us to consider which can be more useful in the application in different situation. Three categories in the classification settled down of ID: a) Instruction in the classroom, b) products for implementation by other users, and c) instructional systems more extensive and complexes directed to problems or goals of an organization. In order to categorize the models, nine characteristics of the ID models are considered: characteristic product in terms of prepared instruction; resources entrusted to the developed attempt, if it is an individual effort or teamwork, the ability and experience that ID delay of the individual or the team, if the instructional materials are selected of the existing resources or represent a design and original product; the amount of realized preliminary analysis, the anticipated technological complexity of development atmospheres and gives, the amount of realized tests and revision, the amount of diffusion and pursuit that happens after the development. This taxonomy is not unique nor is the best one of the classifications ID models but it possible to be concluded that he is useful for the professionals, instructional and educating investigators, and designers in the development of its educative activities.